Employee Performance in the Utilization of E-Office at the Directorate General of Regional Autonomy, Ministry of Home Affairs - Doniman Gavenoreli Daeli; Ahmad Averus; Khasan Effendy (Sean Institute, 2026)
This study aims to analyze employee performance in the implementation of the E-Office system at the Directorate General of Regional Autonomy (Ditjen Otda), Ministry of Home Affairs. Along with the rapid development of information technology, the implementation of E-Office in government institutions is expected to improve employee performance by providing more efficient, effective, and transparent administrative services. However, the adoption of this technology also requires employees to adapt and change their work behavior in carrying out their duties. This research employed a descriptive method with a quantitative approach. Data were collected through a survey involving employees of the Directorate General of Regional Autonomy using a questionnaire designed to measure performance aspects affected by the use of E-Office, including productivity, service quality, and employee satisfaction with the implemented system. Data analysis was conducted using descriptive statistical techniques to describe the extent to which the implementation of E-Office influences employee performance. The results indicate that the implementation of E-Office has indirectly transformed the work structure and organizational culture of employees at the Directorate General of Regional Autonomy, thereby making a significant contribution to employee performance, particularly in accelerating administrative processes. However, its utilization is still considered suboptimal, and improvements are needed in terms of employee mindset transformation and system enhancement, such as reducing paper usage, improving accessibility to information, and increasing socialization efforts. In addition, several challenges remain, including limited technological infrastructure and insufficient socialization and training for some employees, which affect the optimization of E-Office system utilization. This study concludes that although the utilization of E-Office at the Directorate General of Regional Autonomy has contributed to improving employee performance, further efforts are still required in the areas of training, infrastructure development, and increased socialization to ensure the optimal use of the system.